Qualified Economic Growth as an Indicator of Economic Development - Nuraini, Ida; Hariyani, Happy Febrina (Muhammadiyah University Press, 2019)
This study aims to map the districts/cities in East Java that is classified as having quality economic growth, as well as formulating a concept of quality economic growth by examining several social and economic indicators such as unemployment, income distribution across regions, income distribution among economic sectors, equity investment, and poverty.Using Klassen's typology analysis, it is found that most (19 regions) districts and cities in East Java are in the advanced category but depressed. Meanwhile, there are 8 regions that are classified as advanced and growing rapidly and 10 regions are classified as regions that can grow fast and 1 region classified as relatively underdeveloped, namely Tuban District. While the regions that have qualified economic growth are Lamongan District, Jember District, Probolinggo, Madiun, Batu, Blitar, Pasuruan and Mojokerto. Based on the Fix Effect regression model, it can be concluded that the number of industries and Human Development Index have a significant negative effect on economic growth while the contribution of the primary sector has a significant and positive effect on economic growth.